The bank lending channel reconsidered - Alistair Milne; Geoffrey Wood (Bank of Finland, 2009)
It has been widely accepted that constraints on the wholesale funding of bank balance sheets amplify the transmission of monetary policy through what is called the bank lending channel . We show that the effect of such bank balance sheet constraints on monetary transmission is in fact theoretically ambiguous, with the prior expectation, based on standard theoretical models of household and corporate portfolios, that the bank lending channel attenuates monetary policy transmission. We examine macroeconomic data for the G8 countries and find no evidence that banking sector deposits respond negatively and more than lending to tightening of monetary policy, as the accepted view of the bank lending channel requires. The overall picture is mixed, but these data generally suggest that deposits fluctuate procyclically and somewhat less over the business cycle than bank lending, and that total bank deposits, unlike bank lending, show little direct response to changes in interest rates. This suggests it is very unlikely that the bank lending channel amplifies monetary policy. Our paper has thus corrected a misunderstanding about the role of banks in monetary policy transmission that has persisted in the literature for some two decades.
URN:NBN:fi:bof-20140807145
Keywords: 330